Antibacterial Effects and Mode of Action of Selected Essential Oils Components against Escherichia coli and Staphylococcus aureus - Manuel Simões (2015)
Bacterial resistance has been increasingly reported worldwide and is one of the major causes of failure in the treatment of infectious diseases. Natural-based products, including plant secondary metabolites (phytochemicals), may be used to surpass or reduce this problem. The objective of this study was to determine the antibacterial effect and mode of action of selected essential oils (EOs) components: carveol, carvone, citronellol, and citronellal, against Escherichia coli and Staphylococcus aureus. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were assessed for the selected EOs components. Moreover, physicochemical bacterial surface characterization, bacterial surface charge, membrane integrity, and K+ leakage assays were carried out to investigate the antimicrobial mode of action of EOs components. Citronellol was the most effective molecule against both pathogens, followed by citronellal, carveol, and carvone. Changes in the hydrophobicity, surface charge, and membrane integrity with the subsequent K+ leakage from E. coli and S. aureus were observed after exposure to EOs. This study demonstrates that the selected EOs have significant antimicrobial activity against the bacteria tested, acting on the cell surface and causing the disruption of the bacterial membrane. Moreover, these molecules are interesting alternatives to conventional antimicrobials for the control of microbial infections.